PROFIL KINERJA FINANSIAL PERUSAHAAN-PERUSAHAAN YANG GO-PUBLIC DI PASAR MODAL ASEAN - Mas'ud Machfoedz (Faculty of Economics and Business, Universitas Gadjah Mada, 1999)
Almost all companies listed in ASEAN country capital markets have droppedtheir financial performance since the accounting year of 1997. In Indonesia, morethan sixty per cent of companies listed in Jakarta Stock Exchange did not or did notdare to publish their mandatory annual financial statements to avoid publishing theirpoor performance. The similar situation has also been felt by other ASEAN countrycapital markets. The question that was relevant to be raised: are the poor financialperformance of companies listed in the ASEAN country capital markets caused by thesudden crisis or by long experience of poor financial performance?This study intents to answer the above question, whether the crisis or longtimeof poor financial performance caused the company financial problems. Samples weretaken from companies listed in four major capital market of ASEAN, namely:Thailand, Singapore, Malaysia, and Indonesia. Pooled time series data consist of 132data included in the sample for three year periods of 1993, 1994, and 1995 for 44companies. The parametric and non-parametric statistic methods q/